ILIA CHAVCHAVADZE’S VILLAGE STUDIES AND THE PRINCIPLE OF INDIVIDUALITY OF GEORGIAN SOCIETY - Gogatishvili, Mikheil (European Scientific Journal, ESJ, 2014)
We can consider the work of the Georgian thinker and writer Ilia Chavchavadze - "Life and the Law” as one of the first works in village studies. Ilia make deep comparative analysis. It is expressed in fundamental differentiation between Georgian and Russian mode of production. Thanks to Ilia Cavchavadze’s essential analysis, it is ascertained that Georgian mode of production has in bases private property but Russian mode of production - communal ownership. According to Chavchavadze, village society in Russia is established on different base than in Georgia.